Realizing a competitive Doplang tourist village through institutional innovation in local potential development - Mega Novita; Senowarsito Senowarsito; Rifki Hermana; Sutomo Sutomo (Universitas Muhammadiyah Magelang, 2023)
The Covid-19 pandemic has had a significant impact on the tourism sector, including Doplang tourist village, which was recognized as an attractive tourist destination in Semarang Regency. The pandemic situation presented significant challenges that resulted in demotivation among the community in developing the tourism potential of this area. In the context of institutional innovation, this community empowerment aims to address the demotivation of Doplang tourist village's community caused by the Covid-19 pandemic, which disrupted the development of tourism potential. One crucial step in achieving this goal is to implement changes and improvements in the structure and mechanisms of organizations involved in managing the tourism destination in the village. Through institutional innovation, it is expected that more effective collaboration and synergy will be created among all parties involved. These changes aim to enhance active participation from the community in decision-making related to tourism development. Consequently, the community will play a more active role in managing their own tourist destination and collectively identifying the potential of local tourism that can be developed. The outcomes of this program also include efforts to raise awareness within the community about developing local tourism potential and creatively promoting the village through social media. Through effective collaboration among various stakeholders, it is hoped that Doplang tourist village will recover from the impact of the pandemic, increase tourist visits, stimulate the local economy, and strengthen the village's image as a competitive, sustainable, and unique tourism destination.